THE RESPONSE OF DEPOSITS IN THE BANKING SYSTEM TO SHOCKS IN THE MACROECONOMY - Theola, Veliana; Ponziani, Regi Muzio (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study aims at determining the response of deposits (third party funds) in the commercial banks and rural banks to the shocks occurring to inflation, money supply, and USD/IDR exchange rate. So far previous study has mainly focused on only Islamic banks. The data collected were monthly data extending from January 2015 until December 2023. All the data were available on Bank Indonesia and OJK’s websites. The research method used was impulse response function (IRF) that was preceded by vector error correction model (VECM). Upon first examination, it was found out that the data were not stationary. Therefore, they need to be first-differenced for further testing. There was cointegration in the data and therefore we could conclude that banks deposit has a long-term relationship with inflation, money supply, and exchange rate. Impulse response function showed that deposits in the banking system will decrease whenever there is a shock on inflation. This shows how people in the rural and urban areas will hold more cash in the midst of high uncertainty in the economy. Moreover, when there are shocks happening to money supply and exchange rate, the deposits in the rural and commercial banks are very likely to decline. Again, this corroborates the evidence for the tendency of the population to hold more cash in hands to be prepared in times of high uncertainty in money supply and exchange rate.